Evaluation of the static behavior of cable-stayed bridge with a curved pylon: A case study - Duc Thi Thu Dinh NGUYEN; Van Ha MAC (Journal of Materials and Engineering Structures)
Bridges play an essential role in the transportation system, especially large-span bridges. Interestingly, cable-stayed bridges (CSBs), typical large-span bridges, have been applied worldwide with curved pylons to obtain a high aesthetic. However, the effects of the curved pylon on CSB behavior are complicated compared to the traditional cases, e.g., A and H-shaped pylons. Remarkably, the cable tension and internal forces of the girders and pylons were significantly redistributed due to the curvature of the pylons. This motivates this study to quantitatively address the impact of curved pylons on the static behavior of CSBs. The current work also proposes a suitable strengthening solution using additional horizontal beams for the curved pylon. To achieve these goals, numerical simulation is employed to develop 3D CSB models with curved, H, and A-shaped pylons. Moreover, the cable tension force from the numerical simulation and that obtained by the lift-off measurement method for an actual bridge are compared to demonstrate the reliability of 3D models. Thus, the results of the present study are expected to provide more profound knowledge and valuable insights for the design work of future curved pylon CSBs.